2014
DOI: 10.1148/radiol.13130557
|View full text |Cite
|
Sign up to set email alerts
|

Stress Cardiac MR Imaging Compared with Stress Echocardiography in the Early Evaluation of Patients Who Present to the Emergency Department with Intermediate-Risk Chest Pain

Abstract: Purpose:To compare the utility and efficacy of stress cardiac magnetic resonance (MR) imaging and stress echocardiography in an emergency setting in patients with acute chest pain (CP) and intermediate risk of coronary artery disease (CAD). Materials and Methods:Written informed consent was obtained from all patients. This HIPAA-compliant study was approved by the institutional review board for research ethics. Sixty patients without history of CAD presented to the emergency department with intermediate-risk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Few studies have investigated the usefulness of comprehensive CMR imaging in patients with acute chest pain and suspected NSTEMI [22][23][24][25][26][27][28]. Although these studies cannot be compared directly because of differences in study population, design, prevalence of NSTEMI, CMR protocol and outcome measures, they all share a high sensitivity (up to 92%) and specificity (up to 96%).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the usefulness of comprehensive CMR imaging in patients with acute chest pain and suspected NSTEMI [22][23][24][25][26][27][28]. Although these studies cannot be compared directly because of differences in study population, design, prevalence of NSTEMI, CMR protocol and outcome measures, they all share a high sensitivity (up to 92%) and specificity (up to 96%).…”
Section: Discussionmentioning
confidence: 99%
“…67 CMR with adenosine has also been useful to stage risk in patients with acute chest pain in the ER. 68 In patients with a negative stress test, the free of episodes-survival rate after a year of follow-up was significantly greater if there was a perfusion defect in the CMR---adenosine. Therefore, in patients with suspicion of coronary artery disease or known coronary disease, the fact of not finding myocardial ischemia with CMR---dobutamine or vasodilating drugs is a sign of good prognosis.…”
Section: Inducible Myocardial Ischemiamentioning
confidence: 96%
“…The initial CE-MARC study demonstrated that stress CMR was superior to SPECT regarding the diagnostic accuracy for CAD[10]. It has also been shown that compared with stress echocardiography, stress CMR was the strongest independent predictor of significant CAD among patients with intermediate probability of CAD presenting to emergency department[11]. The 5-year follow up data from CE-MARC study demonstrated that stress CMR was the only significant predictor of MACE in addition to major cardiovascular risk factors, angiographic findings or the effect of initial treatment[12].…”
Section: Future Directionsmentioning
confidence: 99%